2014
DOI: 10.1111/cob.12060
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐effectiveness of the LighterLife weight management programme as an intervention for obesity in England

Abstract: LighterLife Total is a very low calorie diet total dietary replacement weight reduction programme that provides Foodpacks, behavioural change therapy and group support appropriate for people with a body mass index of 30 kg m(-2) or above. A model was built to assess the cost-effectiveness of LighterLife Total, compared with (i) no treatment, Counterweight, Weight Watchers and Slimming World, as a treatment for obesity in those with a body mass index of 30 kg m(-2) or above, and (ii) no treatment, gastric bandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(48 citation statements)
references
References 17 publications
0
48
0
Order By: Relevance
“…One study performed the economic analysis of lifestyle changes achieved through e-learning devices [ 32 ]. Another economic evaluation from the United Kingdom was conducted on a program focusing on very low-calorie diets [ 34 ]. Two studies reported on the economic evaluation of interventions consisting solely of physical activity [ 21 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study performed the economic analysis of lifestyle changes achieved through e-learning devices [ 32 ]. Another economic evaluation from the United Kingdom was conducted on a program focusing on very low-calorie diets [ 34 ]. Two studies reported on the economic evaluation of interventions consisting solely of physical activity [ 21 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity analysis, which allows assessing the reliability and the generalizability of the results [ 42 ], was performed in all studies except one [ 34 ]. Over half the studies performed univariate sensitivity analysis and eight studies performed bivariate sensitivity analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty HEMs cited an evidence source for estimated weight loss that reported no measurement of psychosocial variables. [24][25][26][27][28][29][30][31][32][33][35][36][37][38][39][40]42,44,46,[49][50][51][52]55,56,58,59,61,62,68 Psychosocial variables were measured in evidence sources cited in 8 HEMs (Table 3); 4 of these HEMs 43,45,48,53 each based the estimated weight loss on a single trial, but no analyses of the psychosocial variables measured in relation to the intervention or weight change were reported in the trial. Four HEMs 23,34,41,47 cited 5 trials that included some analysis of psychosocial factors.…”
Section: Trial 69mentioning
confidence: 99%
“…Weight loss regained immediately. Eight HEMs [35][36][37][38][39][40][41][42] assumed that the intervention effect ceased after the trial follow-up and that those receiving the intervention immediately returned to the same weight as the control group. From this point onward, there was no weight difference between the intervention and control groups; their weight either remained at that value for the remainder of the time horizon [35][36][37][38][39]42 or followed a natural history trajectory 40,41 (Figure 2b).…”
Section: Assumptions Made About Weight Trajectoriesmentioning
confidence: 99%